Problems of Geocosmos-2022 Proceedings of the XIV Conference and School - Kosterov, Andrei; Lyskova, Evgeniya; Mironova, Irina; Apatenkov, Sergey; Baranov, Sergey (Cham : Springer International Publishing : Imprint: Springer, 2023)
Problems of Geocosmos conference proceedings series provide a snapshot of current research in a broad area of Earth Sciences carried out in Russia and elsewhere. Themes covered include solar physics, physics of magnetosphere, ionosphere and atmosphere, solar-terrestrial coupling links, seismology and geodynamics, paleomagnetism and rock magnetism, as well as cross-disciplinary studies. The proceedings are carefully edited, providing a panoramic outlook of a broad area of Earth Sciences. The readership includes colleague researchers, students and early career scientists. The proceedings will help the readers to look at their research fields from various points of view. Problems of Geocosmos conferences are held by Earth Physics Department, St. Petersburg University bi-annually since 1994. It is one of the largest forums of this kind in Russia/former Soviet Union attracting up to 200 researchers in Earth and magnetospheric physics.
Keywords: Planetary science; Geophysics; Atmospheric science; Planetary Science; Geophysics; Atmospheric Science